Deposition of TiO2 thin films by dip-coating technique from a two-phase solution method and application to photocatalysis - Pedrini, Luiz F.K. [UNESP]; Escaliante, Lucas C. [UNESP]; Scalvi, Luis V.A. [UNESP] (FapUNIFESP (SciELO), 2021)
A derivation of the sol-gel-dip-coating deposition technique is proposed, where the precursor solution exhibits two separated liquid phases, reaching an equilibrium state in a heterogeneous solution. Structural, optical and photocatalytic properties of TiO2 films grown from the proposed two phases method are shown and discussed, along with the properties of films deposited when the top phase present distinct lengths, which are observed through SEM images and optical transmittance spectra. The dominant crystalline phase is anatase for all the films prepared. Films are tested towards their efficiency for photocatalysis, using methylene blue as dye degradation agent. It has been found that films deposited through the two phase method are more efficient on the photocatalyitic degradation of methylene blue.
Keywords: Dip-coating; Photocatalysis; Sol-Gel; Titanium dioxide